Development and production of hop in a high temperature region - Simieli, Matheus Balsalobre (2021)
The objective of this work was to evaluate the development and growth of hop cultivars under high temperature conditions. The work was developed at the Farm of Teaching, Research and Extension the School of Engineering of São Paulo State University (UNESP), Campus of Ilha Solteira in two harvests. The design used was randomized blocks with six treatments (cultivars – Cascade, Millenium, Chinook, Centennial, Magnum and Nugget), and six replications. Plant height, leaf chlorophyll index, number of flowers and flower mass in two crops were evaluated. In the first harvest, the Nugget variety had the greatest growth. The Cascade, Millenium and Chinook varieties did not produce flowers. From those that produced, the cultivar Magnum obtained 132.90 kg ha-1 of flowers. In the second harvest the Cascade and Chinook varieties did not produce flowers. Cultivars Cascade, Millenium, Centennial and Nugget showed the highest growth in height. The Magnum variety produced the greatest amount of flowers (467.33 kg ha-1), followed by the Millenium (290.56 kg ha-1) and Centennial (226.60 kg ha-1) variety. Thus, for the brewing, pharmaceutical or cosmetic industry, the cultivation of the Magnum variety is recommended in the northwest region of São Paulo state, as it produces a greater quantity of flowers. If the purpose is ornamental, the cultivation of the Cascade, Nugget, Centennial and Millenium varieties may be recommended as they show the greatest height development.